A detailed approach to model transport, heterogeneous chemistry, and electrochemistry in solid-oxide fuel cells - Janardhanan, Vinod (KIT Scientific Publishing, 2007)
This book lays out a numerical framework for the detailed description of heterogeneous chemistry, electrochemistry and porous media transport in solid-oxide fuel cells (SOFC). Assuming hydrogen as the only electrochemically active species, a modified Butler-Volmer equation is used to model the electrochemical charge transfer.